100 of the world's best houses - Davis, Jodie.;Strong, Diane.;Slessor, Catherine (Australia : Images, 2002)
Features exciting contemporary houses from some of the greatest architects, including Hugh Newell Jacobsen, Foster and Partners, Rem Koolhaas, Kisho Kurokawa, Eric Owen Moss, Harry Seidler, Steven Ehrlich, Rick Joy and Alberto Campo Baeza. Includes 10 Australian and 4 New Zealand houses.
Introduction -- 11th & Hill Residence / Trout Studios 14 -- Alumbrera / A.J. Diamond, Donald Schmitt and Company 16 -- Ambrosini/Neu Residence / Kanner Architects 18 -- Art House / Brookes Stacey Randall, Architects 22 -- Art-Nouveau Villa / SPATIUM 26 -- Baan Kamonorrathep / Architects 49 30 -- Bartlit Residence / Lake/Flato Architects, Inc. 34 -- Beach House / Brian Healy Architects and Michael Ryan Architects 38 -- Beckhard House / Herbert Beckhard Frank Richlan & Associates 42 -- Bordeaux House / Rem Koolhaas, Office of Metropolitan Architecture 44 -- Brick Bay House / Noel Lane Architects 48 -- Brody House / Singer Architects 50 -- Brooke Coombes House / Burd Haward Marston Architects 54 -- Brouwer House / Adrian Maserow Architects 58 -- Buckwalter House / Hugh Newell Jacobsen, FAIA 60 -- Buena Vista Park Residence / Inglese Architecture 62 -- Burns Residence / Glen Irani Architects 66 -- Burton House / Ahrends Burton and Koralek 68 -- Caner/Beier Residence / Arkin Tilt Architects 70 -- Canyon Residence / Steven Ehrlich Architects 74 -- Cape Schanck House / Denton Corker Marshall 78 -- Carmel House / Cesar Pelli & Associates Inc 80 -- Carter/Tucker House / Sean Godsell 82 -- Carwill House / Kohn Pedersen Fox Associates PC 84 -- Colorado House / Architecture Research Office 88 -- Cozzens Residence / McInturff Architects 92 -- Crescent House / Dr Ken Shuttleworth, Architect 96 -- De Blas House / Alberto Campo Baeza Arquitecto in collaboration with Raul del Valle 100 -- Defeo House Renovation / OJMR Architects 104 -- Dr Manke Residence / gmp -- Architekten von Gerkan, Marg und Partner 106 -- Drake House / Alfredo De Vido Associates 110 -- Drysdale Residence / William Morgan Architects PA 112 -- Gallery for Contemporary Art / Kennedy & Violich Architecture 116 -- Garden House / Olson Sundberg Kundig Allen Architects 120 -- Gibbs House / Parsonson Architects 124 -- Green Street Residence / Six Degrees Architects 128 -- Greenwood House / Helliwell + Smith, Blue Sky Architecture + Planning 132 -- Hamilton House / Harry Seidler & Associates 134 -- Hammond Residence / Clare Design 138 -- Harbor Town Residence / Looney Ricks Kiss 142 -- House 2 for Two Architects / House + House Architects 144 -- House at Toro Canyon / Barton Myers Associates Inc 146 -- House for Sonoran Desert / Swaback Partners 148 -- House for the Future / Jestico + Whiles 152 -- House in Aggstall / Hild und K Architekten BDA 156 -- House in Mt Fuji / Satoshi Okada architects 158 -- House in the Connecticut Hills / Mark Simon, FAIA & James C. Childress, FAIA Centerbrook Architects and Planners 162 -- House in the Hudson Valley / Jefferson B. Riley, FAIA & Charles G. Mueller, AIA Centerbrook Architects and Planners 164 -- House in the Rocky Mountains / Alexander Gorlin Architect 166 -- House Into / Jyrki Tasa 170 -- House rue Robert Blache / Architecture Studio 174 -- Island Vacation House / Pete Bossley Architects 176 -- J Residence / Kim Young-Sub + Kunchook-Moonhwa Architects 180 -- Jackson House / Daryl Jackson Architects 182 -- Jamie Residence / Escher GuneWardena Architecture, Inc. 184 -- Kebbell House / John Daish Architects + The Walls Organisation (T.W.O.) 188 -- Kline Residence / Lorcan O'Herlihy Architects 190 -- Koivikko House / Architect Esa Piironen 194 -- Kronenberg Beach House / Alexander Tzannes Associates 196 -- Lawson-Western House / Eric Owen Moss Architects 198 -- Lewton Residence / Westwork Architects, PA 200 -- Malibu Beach House / David Lawrence Gray Architects 204 -- Malibu Residence / Gwathmey Siegel & Associates Architects 206 -- Mallett House / SITE Environmental Design, Inc 210 -- Marquand Retreat / The Miller/Hull Partnership, LLP 212 -- Marsh House / Marsh & Grochowski 214 -- Maxman Residence / Susan A. Maxman, FAIA 216 -- Mellangoose House / Rod McAllister 220 -- Michaels/Sisson Residence / The Miller/Hull Partnership, LLP 222 -- Moen Residence / Herbert Lewis Kruse Blunck Architecture 224 -- Muskoka Boathouse / Shim Sutcliffe Architects 226 -- n-house / Atelier Hitoshi Abe 230 -- Nomentana Residence / Mack Scogin Merrill Elam Architects 232 -- O Residence / Kisho Kurokawa Architect & Associates 236 -- Outside-In House / Pfau Architecture Ltd 238 -- Poole Residence / Gabriel & Elizabeth Poole Design Company 242 -- Puente Soivio / Siren Architects Ltd 246 -- Riparian House / The Cox Group 250 -- Roof-Roof House / T.R. Hamzah & Yeang Sdn. Bhd. 254 -- Roth Residence / Ace Architects 256 -- Rotunda House / Architects 49 258 -- Roxbury Drive Residence / Arxis Design Studio 260 -- Shapiro Residence / Ray Kappe, FAIA 262 -- Silverman Residence / Rockefeller I Hricak Architects 266 -- Skywood House / Graham Phillips, Architect 270 -- Sloan Residence / McIntosh Poris Associates 274 -- Terner Residence and Entenza Remodel / Barry A. Berkus, AIA 276 -- The Ledge House / Bohlin Cywinski Jackson 280 -- Tree House / Lippmann Associates 284 -- Trillium Springs Farmhouse / Nagle Hartray Danker Kagan McKay Architects Planners 288 -- Turtle Creek House / Antoine Predock Architect 292 -- Tyler Residence / Rick Joy Architects 294 -- Urban Residence / Shubin + Donaldson Architects 298 -- Vacation House in Spetses / Meletitiki-Alexandros Tombazis and Associates 300 -- Villa le Goff / Rudy Ricciotti Architecte 304 -- Villa te Goes / Bedaux de Brouwer Architecten 306 -- Wakeham House / Robert Adam Architects 310 -- Weissberg Residence / Belzberg Architects 312 -- West 22nd Street Residence / Charles Rose Architects Inc. 316 -- Yudell-Beebe House / Moore Ruble Yudell 320.
Includes index.
Keywords: ARCHITECTURE -- DOMESTIC